Evaluation of Stakeholders’ Expectations Towards Congress Tourism by Kano Model: Case of Nevşehir - Karakuş, Yusuf; Çoban, Suzan (Anais Brasileiros de Estudos Turísticos, 2018)
In the study, it is aimed to evaluate and weight the expectations of tourists for congress tourism in terms of Nevşehir destination. The Kano model was used as the basic method in the research. At the same time, the Analytical Hierarchy Process (AHP) has been integrated into the Kano model. In total, data from 90 participants were used. For the Nevşehir destination, the criteria obtained from the literature are weighted using Kano model and AHP. In this context, the highest expectation for convention tourism in Nevşehir destination is the option of "establishing congress visitor’s office" and "improving technical equipment of existing congress halls". Other options are ranked according to importance. According to the findings of the study, expectations for congress tourism in Nevsehir destination were evaluated. On the basis of these evaluations, by the Kano model, if the expectations of the stakholders’ are met comments can be made about the degree to which the satisfaction of the destination will be affected. At the same time, due to the weighting of the activities that can be done towards the congress tourism expectancies, the suggestions that the destination decision makers can use are presented. As a method, it is proposed as a tool that can be used by decision makers. In terms of the method used, the fact that there is no study evaluating tourist expectations for destinations increases the importance of this study. Obtained findings, enables decision-makers in a destination offers a tool that they can use in decision-making. At the same time, the method is suggested to tourism researchers and tourism decision makers in this area